Experimental study on method for rapid determination of COD in wastewater effluents by mercury-free open-tube - WENG Di; XIE Xiao-mei (浙江大学学报. 农业与生命科学版)
A mercury-free and open-tube method was given for determining COD rapidly, which was reliable, simple and safe. The method employs K2Cr2O7 as oxidant in a medium of H2SO4-H3PO4, with catalysis by Ag2SO4 and with addition of AgNO3 and CrK (SO4)2·12H2O to mask chloride. Samples were digested in glass tubes and heated at 160-165℃ for 15 min in an attemperator. The residual dichromate was then determined by titration or spectrophotometry. The results showed that the detection limit for COD was 10.9 mg/L and in the range of 40～800 mg/L COD values of the detected results were satisfied. When the COD concentration was about 85 mg/L, the maximum acceptable value for the chloride would be 1500 mg/L. The advantage of this method avoid using toxic mercuride that could pollute the environment. The developed method has been successfully applied to determine COD in large quantities of wastewater effluents samples.